The impact of hypertension on sexual functions among women - Maria Ciechacka; Agnieszka Pawełko; Ewelina Bąk (Journal of Education, Health and Sport)
Introduction. Human sexuality is an important factor in personality development. It is usually a positive driving force in the human population, motivating people to establish contacts and interpersonal bonds. The "gold standard" for screening tests for sexual disorders in women is currently the Female Sexual Function Index (FSFI). Particularly focusing on patients with hypertension can bring significant results.